2007
DOI: 10.3171/foc-07/08/e1
|View full text |Cite
|
Sign up to set email alerts
|

Minimal tethered cord syndrome: what's necessary to justify a new surgical indication?

Abstract: ✓Traditionally, surgical division of the terminal filum (filum terminale) has been reserved for patients with imaging-apparent spinal cord tethering. The occurrence of medically refractory voiding dysfunction of neurogenic origin, without magnetic resonance (MR) imaging documentation of abnormality in the spine, has been termed “minimal” tethered cord syndrome (TCS). The rationale for and utility of using surgical division of the terminal filum in the treatment of minimal TCS are unproven. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Histological studies have suggested that fila obtained from patients with occult TCS may be more fibrotic than normal [58,61,78], lending support to the notion that a normally positionedCMD could be tethered by a tight or inelastic FT [60,66,72,78]. This hypothesis is supported by the following findings in the current report: [1] the width of the FT decreased steadily as the CMD ascended during growth and development; [2] most patients with normal position of the CMD had positive FT traction tests; [3] at surgery, the FT appeared as a thin, taut, immobile structure that was associated with lateral packing of the cauda equina and reduced regional CSF flow; and [4] immediately after SFT, there was marked distraction of the divided ends, normalized distribution and movements of the cauda equina and increased regional CSF flow (see Fig.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Histological studies have suggested that fila obtained from patients with occult TCS may be more fibrotic than normal [58,61,78], lending support to the notion that a normally positionedCMD could be tethered by a tight or inelastic FT [60,66,72,78]. This hypothesis is supported by the following findings in the current report: [1] the width of the FT decreased steadily as the CMD ascended during growth and development; [2] most patients with normal position of the CMD had positive FT traction tests; [3] at surgery, the FT appeared as a thin, taut, immobile structure that was associated with lateral packing of the cauda equina and reduced regional CSF flow; and [4] immediately after SFT, there was marked distraction of the divided ends, normalized distribution and movements of the cauda equina and increased regional CSF flow (see Fig.…”
Section: Discussionmentioning
confidence: 95%
“…1A), moved rostrally by arithmetic progression during growth and development from a mean of 28.2 mm ± 8.9 SD at 0 to 3 years of age to a mean of 21.2 ± 11.8 SD at maturity. There were no significant differences in the position of the CMD in patients with CM-I/TCS, LLCT/TCS, and healthy control individuals after the age of 8 years, although the measurements had large SDs that are common to normal distribution curves [60]. In patients between the ages of 0 and 7 years, the position of the CMD was low as compared to healthy control individuals (mean, 28.3 and 23.1 mm, P < .01, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Although controversial, recent trends favoring more aggressive surgical approaches for children with minimal or no imaging abnormalities, but clinical symptoms of tethering such as neurogenic bladder, have produced encouraging results in some series. A thorough history and physical examination is crucial in evaluating young patients who present with neurological or urological signs or symptoms suggestive of tethering, even with unremarkable imaging studies [7,8,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…The OTCS case series reported previously that supported the efficacy of surgery was generated by Class III studies. 20 The present study also has limitations in that it is not a randomized casecontrol study and the efficacy of sensitivity or specificity is unclear in our MRI method. Therefore, a prospective randomized trial should be completed to clarify the surgical indications.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, a prospective randomized trial should be completed to clarify the surgical indications. 20,22,24 Principal symptoms and signs of TCS are urinary dysfunction, low-back pain, leg pain or sensory disturbance, and spinal stiffness. 1,[9][10][11]27 Our new method of prone MRI is simple and noninvasive.…”
Section: Discussionmentioning
confidence: 99%